Determinación del nivel de cumplimiento tributario en las compañías de transporte de combustible de la ciudad de Loja, períodos 2020-2021. - Calderón Calderón, Gabriela Rosmery (2022)
The curricular integration work entitled: "Determination of the level of tax compliance within fuel transport companies in the city of Loja during the period 2020-2021", aimed to analyze the tax obligations of the companies, evaluating their compliance in accordance with the current legal regulations. The causes that generated tax noncompliance were identified by developing a compliance analysis report in order to demonstrate the degree of performance of tax obligations and tax liabilities. The study adopted a mixed-methods research approach with a descriptive scope to gain a better establishment and determination of the evaluation. The observation technique was used. Likewise, data collection was obtained by means of a semi-structured interview, which was applied to the management and accounting department. This department facilitated the collection of information and contributed to the fulfillment of the objectives of this study. The identification of the tax regulations was carried out based on the Constitution of the Republic of Ecuador and mainly on the Organic Law of the Internal Tax Regime, regulations and resolutions. These actions allowed to carry out the verification of compliance by concepts of VAT declaration, income tax, withholdings at the source and annexes in order to determine if the companies comply with their obligations in accordance with the regulations. A Tax Compliance analysis report was prepared, which contains objectives, scope, results and general conclusions. Finally, reliable, and timely information was obtained from the analysis applied to the companies. Among the results, there was found the lack of appropriate internal control and training by the directors of the companies, as well as the causes of non-compliance that are of external and internal such as: economic instability in the country, economic crisis with the COVID 19 pandemic, increase in fuel prices, economic losses, lack of training, high levels of indebtedness, poor economic management, affecting the moment compliance is reflected in the declarations received by the Internal Revenue Service.